Uncontrolled per rectal bleeding in chronic myeloid leukaemia: a mere coincidence or a dangerous sign report of an unusual case - Ali, S. Manwar; Singh, Pradeep K.; Joshi, Pranav B.; Naik, Prabhash K. (International Surgery Journal, 2020)
Bleeding haemorrhoids present commonly to surgical outpatient departments (OPDs) and sometimes in emergency. Most often conservative management suffices but infrequently the patients can land up in emergency operation theatre for uncontrolled bleeding. Some haematological disorders can also present with rectal bleeding and amongst them Chronic myeloid leukaemia (CML), a haematological malignancy, presenting as bleeding per rectum has been not been reported so far, though instances of CML with gingival bleed, epistaxis have been reported. CML per se is known to be asymptomatic (40% cases) and bleeding is rarely seen. Here we present an interesting case of an emergency hemorrhoidal bleed that was subsequently diagnosed as CML. The patient after failed conservative management for bleeding haemorrhoids was taken up for emergency haemorrhoidectomy and again a relook under general anaesthesia in the post-operative period as he continued to ooze. The total leucocyte counts which were initially high continued to rise further and the bone marrow examination was reported as chronic myeloproliferative neoplasm and the excised mass was consistent with haemorrhoids. Rectal bleeding associated with CML is so far unreported even though bleeding is seen due to platelet dysfunction from gums and nose in chronic phases of the disease. A high index of suspicion is needed particularly with deranged haematological parameters for considering a diagnosis of these rare presentations. and anaesthesia.